Kunstmanifestatie Open Ateliers Amsterdam-Oost. (Amsterdam : Stichting Outline, 1995)
Jansen, Steven ; Paauw, Rick ; Smarius, Marcel ; van Vugt, Erik ; Brüggen, Thea ; Jurriaans, Marion ; van Rijn, Monica ; Kooter, Jaqueline ; Thule, Stichting Ultima ; Viebre, Egon ; Marouf, Essam ; Ezzat, Shawky ; Dihaj, Bouchaib ; Abdaoui, Latif ; Smit-Houtkoop, Hennie ; Stelt, Huib Van Der ; Veeninga, Mette ; Kletter, Sander ; van Rees, Jan Theun ; Holman, Marcia ; Van Arkel, Jan ; Aschkenasy, Yair ; Molier, Marion ; De Jong, Jeltje
biografie
Open Ateliers Amsterdam-Oost, 4 & 5 november 1995
kunstcatalogus